Interference of retroviral envelope with vaccine-induced CD8+T cell responses is relieved by co-administration of cytokine-encoding vectors - Bongard, Nadine; Lapuente, Dennis; Windmann, Sonja; Dittmer, Ulf; Tenbusch, Matthias; Bayer, Wibke (Retrovirology, 2017)
BACKGROUND: Retroviral envelope (Env) proteins are known to exhibit immunosuppressive properties, which become apparent not only in retroviral infections, but also in gene-based immunizations using retroviral immunogens, where envelope interferes with the induction of CD8+T cell responses towards another, simultaneously or subsequently delivered, immunogen. RESULTS: In the Friend retrovirus mouse model, immunization with a plasmid encoding the Friend murine leukemia virus (F-MuLV) Leader-Gag protein resulted in induction of a strong GagL85-93-specific CD8+T cell response, while the response was completely abrogated by co-immunization with an F-MuLV Env-encoding plasmid. In order to overcome this interference of retroviral envelope, we employed plasmids encoding the cytokines interleukin (IL) 1β, IL2, IL12, IL15, IL21, IL28A or granulocyte-macrophage colony-stimulating factor (GM-CSF) as genetic adjuvants. Co-application of plasmids encoding IL2, IL12, IL21, IL28A and especially GM-CSF rescued the induction of GagL85-93-specific CD8+T cells in mice vaccinated with FV Leader-Gag and Env. Mice that were immunized with plasmids encoding Leader-Gag and Env and the cytokines IL1β, IL12, IL15, IL28A or GM-CSF, but not Leader-Gag and Env without any cytokine, showed significantly reduced viral loads upon a high-dose Friend virus challenge infection. CONCLUSIONS: Our data demonstrate the potency of cytokine-encoding vectors as adjuvants and immune modulators in composite vaccines for anti-retroviral immunization.
EVALuna2:33766